Interconnected factors in EFL engagement: classroom climate, growth mindset, and achievement goals - Ma, Weiran; Yang, Weian; Bu, Qinggang (Frontiers in Psychology, 2024)
This study investigates the relationships among classroom climate, student growth mindset, achievement goal orientation, and student engagement within the context of English as a foreign language (EFL) education in China. Data were collected from 587 Chinese undergraduate EFL students using a questionnaire that assessed their perceptions of classroom climate, growth mindset, achievement goal orientation, and student engagement. Structural equation modeling (SEM) was employed to examine the interplay among the constructs. The results revealed significant positive correlations among all variables, indicating their interconnectedness in the EFL context. Moreover, the SEM analysis confirmed that both classroom climate and growth mindset directly and positively predicted student engagement. Importantly, achievement goal orientation was found to mediate the relationship between both classroom climate and student engagement, and growth mindset and student engagement. The findings have practical implications for EFL educators, emphasizing the need to cultivate a positive classroom climate and promote masteryoriented goals to enhance student motivation and facilitate successful language acquisition.